Behind Closed Doors: The Law and Politics of Cabinet Secrecy. - Campagnolo, Yan (UBC Press, 2021)
Behind Closed Doors asks - and answers - whether the doctrine of Cabinet secrecy still has a role in the Westminster parliamentary system.